Hukum wanita haid ziarah kubur dalam perspektif islam - Diva, Fara (Maliki Interdisciplinary Journal, 2023)
Normal women will experience a monthly cycle known as menstruation or menstruation. There is an opinion that it is not permissible for a menstruating woman to visit the graves, while visiting the graves itself is a visit to pray and take lessons that one day all will return to Him. Visiting the graves that are prohibited are worshiping and asking grave experts. The existence of this triggers a difference of opinion among scholars. Some scholars agree that there are no provisions regarding the law of visiting graves when they are sacred or when they are menstruating.